Impactos na malha de poder resultantes da reestruturação organizacional em uma empresa multinacional química - Figueira, José Carlos Gonçalves (2011)
The corporate environment is a rich field for power disputes. The aim of the current study is to analyze the impacts in the relations of power between the managers of a multinational chemical company, due to an organizational restructuring occurred in 2007. The research work is organized in introduction, five chapters and final considerations. The first two chapters discuss the theoretical framework, presenting the power under the Machiavelli perspective, and the organizational structure under the point of view of the major authors who have dedicated themselves to the subject. The third chapter presents the description of the analyzed company, the Brazilian subsidiary of a multinational in the chemical sector, publicly traded and headquartered in Houston, United States. The fourth chapter covers the methodological procedures, showing that the data was collected in two rounds of interviews in 2009 and 2011 - with the directors and managers of analyzed company. The evolution of the relationships and the power disputes are analyzed based on the data obtained in these two moments. The literature review and the analysis of the data made in the fifth chapter suggest that the company promoted the organizational restructuring to avoid concentration of power in one position. This process was developed with poor planning and organization, resulting in serious conflicts between the directors and managers, who sought the power to accomplish their managing projects